Perception of attenders of urban parks Garanhuns – PE during the COVID-19 pandemic (Research, Society and Development, 2022)
The contamination by the new coronavirus has provoked reflections and questions about the transformations that the city has been going through during this period. And knowing that green areas are important for the lives of the population residing in urban centers, the study aimed to verify through an interview during the COVID-19 pandemic period how regulars perceive and use urban parks, in addition to a interview with park administrators. Thus, it was possible to identify that the parks receive daily the population that lives nearby, in addition to tourists. It was found that in Parque Euclides Dourado there were more female respondents, aged between 18 and 24 years, with single marital status, while in Parque Ruber Van Der Linden users are more often male, aged 35 years. to 44 years, with single marital status. And that parks are valued by their visitors, as they are perceived and used for providing social and environmental function, in addition to offering leisure and health promotion, thus contributing to the quality of life of their users. However, better planning of the suitability of the interior of the parks for the use of the population is necessary, since there was a difference in the adaptation of these spaces during the pandemic period. In this way, the research also aims to contribute to the guidelines to be developed by public managers, with the intention of subsidizing appropriate protocols for the population that uses these spaces.